2018
DOI: 10.1093/heapro/day068
|View full text |Cite
|
Sign up to set email alerts
|

Implementation trial of school staff health promotion: Polish experiences

Abstract: The paper presents the results of the trial implementation of staff health promotion in the Health Promoting Schools (HPS) programme in Poland. The design and key results of the summative evaluation of the 3-year project and activities of schools after completion of the project are described. Over 900 teachers and non-teaching employees from 21 schools participated in the project. Its purpose was to verify the schools' ability to take action related to the promotion of staff health in the HPSs in Poland. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…To overcome these limitations, Poland, for example, has attempted a new project that includes promoting the health of teachers by expanding the existing student-centered health promotion activities. The investigators found that healthcare knowledge had increased among most of the staff following the intervention and that healthy behaviors among the staff had increased as well [47]. More efforts should be added for direct intervention to promote teachers' health behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these limitations, Poland, for example, has attempted a new project that includes promoting the health of teachers by expanding the existing student-centered health promotion activities. The investigators found that healthcare knowledge had increased among most of the staff following the intervention and that healthy behaviors among the staff had increased as well [47]. More efforts should be added for direct intervention to promote teachers' health behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Schools are the best settings for encouraging children's physical activity [46]. Although teachers are exposed to these environments, teachers' physical activity may still be low because school policies to improve teachers' health are lacking [47]. The lack of policies to improve teacher health may be due to teachers being viewed as resources that are not the proper subject of school health efforts [48].…”
Section: Discussionmentioning
confidence: 99%
“…e development of HPS in Poland was closely linked with the evolution of the concept in Europe. It's main directives were set by the resolutions/positions of four European Conferences on Health Promoting Schools (Halkidiki, 1997;Egmond, 2002;Vilnus, 2009;Odense, 2014) (Woynarowska-Sołdan, 2015). Over the last decade, the course of HPS activities was guided by the pillars and values of the approach adopted by the SHE network (SHE, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…School is not only a place of learning for students; it is also a workplace for many employees. IJSE e possibilities of taking such actions, implementation strategies and outcomes were evaluated in Poland as part of the project "Promoting health of sta members in health promoting schools" (2012)(2013)(2014)(2015), carried out at 21 schools (Woynarowska-Sołdan, 2016;Woynarowska-Sołdan, 2018). It's theoretical underpinnings included: the concept of health promotion with its speci c approaches and values; the fundamental theories of the settings approach and concepts for changing health-related behaviour (Woynarowska-Sołdan, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation